Spasial TB. Paru BTA (+) Pada Puskesmas Hc. Kedaton Kecamatan Kedaton Bandar Lampung - Helina Helmy; Adam Irwansyah Fauzi; Enro Sujiton (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Mycobacterium tuberculosis is characterized by a thick, mycolic acid–rich cell wall that confers hydrophobicity, chemical resistance, and environmental stability, making cell wall biosynthesis inhibitors a major therapeutic target. Tuberculosis is not only a medical condition but also a social disease linked to high population density, malnutrition, and limited healthcare access. In 2023, Kedaton District was identified as the most densely populated area in Bandar Lampung, increasing the likelihood of pulmonary TB smear-positive (TB.Paru BTA+) transmission. Aerosol spread is highly distance-dependent: direct exposure within 0–1 meter poses very high risk, and WHO reports indicate that exposure <1 meter for ≥15 minutes in enclosed spaces significantly elevates infection risk, extending up to 5–10 meters without ventilation. This study employed spatial analysis to measure inter-household distances among 75 TB.Paru BTA(+) patients using Euclidean distance and smartphone-based field surveys. The method proved suitable for small-scale studies with high data accuracy, though resource-intensive for larger populations. Findings revealed some households only 3 meters apart, but this observation was not yet statistically significant to confirm transmission dynamics.